Radiological and functional outcome of unstable intertrochanteric fractures treated with proximal femoral locking plate - Singh, Chanchal Kumar; Deshpande, Juhi (International Journal of Research in Orthopaedics, 2021)
Background: Intertrochanteric fracture is a common orthopaedic injury sustained in elderly population because of osteoporosis and trivial fall. Life threatening systemic complications occur mainly due to immobility. Methods: We included 62 patients (40 males and 22 females) of unstable intertrochanteric fracture (AO 31 A2 and A3) attending Department of Orthopaedics. They were all subjected to surgical treatment with proximal femoral locking plate. Patients were followed up at 3rd, 6th and 12th month for outcomes variables i.e.; functional (Harris hip score, Palmer and Parker mobility score) and radiological outcomes (neck shaft angle, loss of reduction, union and implant related complications). Statistical analysis was done using Friedman’s test after calculating the data in terms of mean and median using SPSS 20 software. Results: Mean age of our patients was 64 years, 40 were males and 22 females. 50 patients sustained fracture due to trivial fall and 12 due to RTA. 35 out of 62 patients had medical co-morbidites. 26 patients needed open reduction of fracture and 36 were close reduced. 22 of patients had severe comminution (AO A 3 III type). Average blood loss was 254 ml. Mean degree of loss of reduction was 5 degrees in 6th month and 4 degrees in 12th month. Union was achieved in 48 out of 50 patients at 12th month. Most of the patients achieved fair to good functional outcome scores at 12th month of follow up. We noticed difficulties in fracture reduction as well as complications related to implant. Conclusions: PFLP is an effective implant in comminuted intertrochanteric fractures with broken lateral wall. Complications can be minimised by following principles of locking plate meticulously.